The Music of Malaysia the classical, folk and syncretic traditions - Matusky, Patricia Ann; Tan, Sooi Beng (Abingdon, Oxon Routledge, 2017)
"The book categorizes the types of music genres found in Malaysian society and provides an overview of the development of music in that country. Analyses of the music are illustrated with many examples transcribed from original field recordings. Genres discussed include theatrical and dance forms, percussion ensembles, vocal and instrumental music and classical music. It is an excellent introduction to and exploration of the country's vibrant musical culture"--Back cover.
"An Ashgate book"--Front cover.
"First edition published by Ashgate 2004."
Includes bibliographical references and index.
Keywords: Music -- Malaysia -- History and criticism